Relasi Tanda pada Karakter Tokoh dalam Novel Rara Mendut Karya Y.B Mangunwijaya dan Kontribusinya Terhadap Pembelajaran Sastra di Sekolah Menengah Atas - Nurwahidah Nurwahidah; Kembong Daeng; Andiagussalin Aj (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to describe the shape of the sign relations on character characters in the form of icons, indexes, and symbols as well as the contribution of novel  Rara Mendut analysis to literature learning in high school. This research is a qualitative research using a literary semiotic approach with C.S. Peirce’s sign theory. The data source in this study is the novel Rara Mendut by Y.B. Mangunwijaya. The data of this research is written data in the form of words, clauses and sentences contained in the text of the novel. Data collection techniques used in this study is documentation, reading, and note-taking techniques. Data analysis techniques in this study is data reduction, data presentation, conclusions and data verification. The results of this study found that the figure of Rara Mendut as an icon of a brave and steadfast woman, the Pranacitra figure as a clever human icon, and the figure of Tumenggung Wiraguna as an icon of arbitrary ruler. The index found in this study includes the rejection of the of Rara Mendut character  againts the proposal of the Tumenggung Wiraguna character and the true love story of the character Rara Mendut and Pranacitra. The symbols in this study is a symbols of Javanese culture that is thickly used by the characters in the novel. The results of this study can contribute as an alternative teaching material for learning literature in high school.